THE BITTER-HONEY NATURE OF TRADITIONAL MYTH PRACTICES IN SOUTH-SOUTH NIGERIA: THE CASE OF KABANGATENDE CULT OF OBUDU COSMOLOGY IN CROSS RIVER STATES - Angela A. Ajimase; Peter Akongfeh Agwu (Social Sciences, Humanities and Education Journal (SHE Journal), 2021)
Every way of life, whether Asian, European or African, is traditional by nature. This corpus explores contradictions inherent in the traditional practice of the myth of the Kabangatendé cult of Obudu in Cross River State, Southern Nigeria. The myth presents an image of positive effects on human practitioners, leading to a consistent increase in money, social influence and political strength. It is also said to be a symbol of affluence, nobility, auspiciousness, success and prosperity with less effort. It is imperative to note that myths operate in diverse capacities. Some are authoritative and appear to have a compelling force of obedience on the people, while others are manipulated and their influence on custodians can be termed to befit situations. This study seeks to address the following questions: Is the Kabangatende cult a revolutionary myth that militates against human existence? Does this myth halt the economic, social and political transformation of its custodians? Or is it an artistic reality that favors literary aesthetics that in turn promote Obudu tradition? In an attempt to arrive at possible tentative responses to the interrogations raised, the paper hinges on Joseph Campbell’s theory of monomyth and other theories whereby empirical evidence will be drawn from ethnographic and historical research, interviews and observations. This study contributes in a better understanding on how traditional practices, with counter-productive tendencies notwithstanding, can be adhered to by the people.